2006
DOI: 10.1017/s1352465806002839
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Depressive Relapse During a Two Year Prospective Follow-up after Cognitive and Behavioral Therapies

Abstract: Patient characteristics may partly explain individual differences in long-term maintenance of treatment gains in response to cognitive and behavioral therapies (CBT). This study evaluated the relative contribution of negative cognitive style, behavioral activation, and personality patterns, measured at the end of treatment among treatment responders, towards the risk of relapse of major depressive disorder over a 2-year prospective follow-up. The sample included depressed adults who were randomized and receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…About half of patients with MDD treated with behavioral psychotherapy report partial treatment response (Gollan, Gortner, & Dobson, 2006), and up to 75% achieve response or remission at long-term follow-up after a course of behavioral therapy (Dimidjian et al, 2006; Hopko et al, 2011). Identifying predictors of positive changes during behavioral therapies will improve our understanding of differential course of improvement during treatment.…”
Section: Introductionmentioning
confidence: 99%
“…About half of patients with MDD treated with behavioral psychotherapy report partial treatment response (Gollan, Gortner, & Dobson, 2006), and up to 75% achieve response or remission at long-term follow-up after a course of behavioral therapy (Dimidjian et al, 2006; Hopko et al, 2011). Identifying predictors of positive changes during behavioral therapies will improve our understanding of differential course of improvement during treatment.…”
Section: Introductionmentioning
confidence: 99%
“…As such, it may be that people who report receiving less enjoyment from the experience of pleasant events may be less likely to benefit from behavioral treatments for depression. In support of this perspective, Gollan et al (2006) reported that lower enjoyment of pleasant events, but not frequency of pleasant events, was associated with higher relapse rates following cognitive and behavioral treatments of depression. Although there has been little research on predictors of outcome specifically on behavioral treatments for depression, the current findings suggest that genetic vulnerability, as evidenced by family history of depression or presence of genetically-influenced personality traits (e.g., high neuroticism, low positive emotionality), may predict poorer response to BA or higher relapse rates following BA.…”
Section: Discussionmentioning
confidence: 92%
“…Although there has been little research on predictors of outcome specifically on behavioral treatments for depression, the current findings suggest that genetic vulnerability, as evidenced by family history of depression or presence of genetically-influenced personality traits (e.g., high neuroticism, low positive emotionality), may predict poorer response to BA or higher relapse rates following BA. In partial support of this perspective, Gollan et al (2006) found that a higher level of dependent personality traits was associated with greater likelihood of relapse following cognitive and behavioral treatments of depression, and that the association between enjoyment of pleasant events and depressive relapse was no longer significant when controlling for dependent personality. Therefore, to the extent that genetically influenced traits contribute both to the experience of pleasant events and depression, then individuals with high genetic vulnerability for depression may be less likely to respond to and more likely to relapse following behavioral treatments for depression.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Patient predictors of positive treatment response for BA include a lower endorsement of existential reasons for depression (Addis & Jacobson, 1996); higher depressive severity (Dimidjian et al, 2006), limited comorbidity, being married (Colman et al, 2009), and diminished hostility (Gollan, Gortner, & Dobson, 2006). BA responders show an increased activation of a brain region involved with affective responses to positive and negative stimuli (paracingulate gyrus) and with cognitive flexibility (Dichter et al, 2010; Dichter, Felder & Smolski, 2009).…”
mentioning
confidence: 99%